The effects of sugar imports from Ukraine on markets and stakeholders in the EU: Study prepared for the InfoZentrum Zuckerverwender (IZZ) - Stephan von Cramon-Taubadel; Oleg Nivievskyi (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2024)
In 2016 the EU granted Ukraine trade preferences in the form of tariff rate quotas (TRQs) for agricul- tural products including sugar under the Deep and Comprehensive Free Trade Agreement. In June 2022 in response to Russia's attack on Ukraine, the EU extended these preferences to full liberalisa- tion of sugar trade under the so-called Autonomous Trade Measures (ATMs). Prior to 2022, EU imports of sugar from Ukraine were sporadic and never amounted to more than 11% of total EU imports in any given month. However, in late 2022 in response to the ATMs, EU imports of white sugar from Ukraine increased, and by late 2023 and early 2024 Ukraine was supplying over 50% of the EU's monthly sugar imports. [...]
Keywords: 330; Sugar; Import; Sugar market; Stakeholders; Ukraine; EU countries; Zucker; Import; Zuckermarkt; Stakeholder; Ukraine; EU-Staaten